Distimia: videojuego de lógica y plataformas (2020)
Dysthymia is a 2D platformer, logic, and adventure video game developed in the Unity engine, which implements pixel art for its graphics, developed in conjunction with Juan Pablo Perez, who was in charge of the art direction. It offers a look at creative repression, through an environmental narrative inspired by personal experiences and the exploration of innovative mechanics and controls. The latter seeking to find the balance between environment, narrative, fun, and challenge. The player is put in the shoes of an infant who lives in an environment of constant academic pressure from his parents, who exert creative repression on him since ?he distracts? from the goals they have set for him. Due to stress, the protagonist develops a series of psychological conditions such as introversion, depression, fear of loneliness, and darkness, better known as Persistent Depression Disorder.